Bats - Mikkola, Heimo (IntechOpen, 2018)
Bats have a poor image for the public at large because they are often feared. This is usually due to ignorance. In this book, we have eight chapters on bats covering countries such as Algeria, Bulgaria, France, Pakistan, Poland, the UK and the USA and subjects ranging from acoustic monitoring of bat species for distribution and conservation purposes to various bat-borne and bat-carried diseases. These diseases cannot be taken lightly but should not be a reason for panic or to fear or even kill bats. Bats will not cause any harm if we let them live in peace. With the added knowledge through this book, we should know how best to cope with bats, which need all our support in the changing environments and climates.